A marketingstratégiák készítésének jellegzetes problémái: az ezredfordulón és most - Józsa, László (Marketing & Menedzsment, 2017)
The entrepreneurships are interested in the future changes, they would like to know the directions of the challenges. Because of that planning is becoming more important. It turned out that a good plan can conduct them to the success. In this article, the author summarises the potential problems of the different methods used in strategic marketing planning concentrating for the problems of STEEP analyses, competitive analyses, SWOT and the analyses of the customer demand. It demonstrates the potential solutions of each mentioned problem. In the last part, the economic actuality of the questions is shown emphasizing the long-term existence of the planning problems in the Hungarian economy. The critical point is the relationship between the state and the entrepreneurships because in many situations Hungarian economy is not market-driven, but political situation-driven.